Underspecification in Degree Operators. (9th January 2018) - Thomas, Guillaume
Abstract: The goal of this article is to account for the recurrent homophony between comparison, additivity and continuation cross-linguistically. Building on Roger Schwarzschild's recent work on comparison in scale segment semantics, I propose that comparative, additive and continuative sentences all assert the existence of a rising scale segment, and differ in terms of (i) the nature of the scale and (ii) the identification of the extremities of the scale segments. At a morphosyntactic level, all three types of sentences involve the combination of a feature that denotes a property of rising scale segments with other features whose denotations constrain the identification of the extremities of the segments in a way that is characteristic of each interpretation (additivity, comparison or continuation). Homophony results from the underspecification of Vocabulary Items in Distributed Morphology.